Prediction of corrosion rate in SA 283 material affected by differences soil type in controlled environments. Issue 1 (June 2019) - Putra, Reza; Muhammad; Huzni, Syifaul; Fonna, Syarizal
Abstract: Research has been done on corrosion rates growth in SA 283 material which is influenced by differences in soil types in controlled environments. A283 grade D materials which are carbon steel formed into pipes with a diameter of 30" which is used to distribute raw water for industrial needs. Weight loss methods that are in accordance with the ASTM G 162 standard have been used in this study. The buried time of the test specimen is 720 hours as one of the variables in calculating the value of the corrosion rate that occurs. The study was conducted at the Laboratory by controlling the soil structure, reducing potential, moisture level, soil pH level so that it did not change. The results of the study on soil types with a potential redox value of 60.6 mV with a pH level of 5.67 showed the greatest corrosion rate in material A283 that is 19.67 MPY or equal to 0.499 mm/yr. The results of this study concluded that the type of soil and its environment greatly affect the corrosion rate of carbon steel, so special attention is needed in protecting the pipe from corrosion attack.